A re-evaluation of forces in swimming - Rushall, B. S.; Sprigings, E. J.; Holt, L. E.; Cappaert, J. M. (Journal of Swimming Research, 1994)
Convincing arguments and documentation lead to the conclusion that drag forces, and not lift forces, constitute the major proportion of propulsive forces in swimming. It is asserted that the arguments in favor of lift dominance were ill-conceived. It is proposed that the forearm contributes more to propulsion than does the hand, particularly as swimming velocity increases. Because of its shape, most forearm propulsion must be a drag force. Added to this is the fact that the forearm follows a much straighter path than the hand. With the hand and forearm moving as a propulsive "surface" the often proposed notion that the hand moves much faster than the forearm is contradicted. Propulsion only occurs in part of the underwater movement and in crawl stroke that is when the overall movement is linear and horizontal. The entry and exit actions are considered simply as positioning movements to better situate the propulsive surface to create or terminate propulsive force applications. Implication: The theoretical bases for describing propulsive forces in competitive swimming strokes that have been in vogue since 1970 are wrong.